Recommendations for wider adoption of clinical pharmacy in Central and Eastern Europe in order to optimise pharmacotherapy and improve patient outcomes - Urbańczyk, Kamila; Guntschnig, Sonja; Antoniadis, Vasilis; Falamic, Slaven; Kovacevic, Tijana; Kurczewska-Michalak, Marta; Miljković, Branislava; Olearova, Anna; Sviestina, Inese; Szucs, Attila; Tachkov, Konstantin; Tiszai, Zita; et al. (Frontiers in Pharmacology, 2023)
Clinical pharmacy as an area of practice, education and research started developing around the 1960s when pharmacists across the globe gradually identified the need to focus more on ensuring the appropriate use of medicines to improve patient outcomes rather than being engaged in manufacturing and supply. Since that time numerous studies have shown the positive impact of clinical pharmacy services (CPS). The need for wider adoption of CPS worldwide becomes urgent, as the global population ages, and the prevalence of polypharmacy as well as shortage of healthcare professionals is rising. At the same time, there is great pressure to provide both high-quality and cost-effective health services. All these challenges urgently require the adoption of a new paradigm of healthcare system architecture. One of the most appropriate answers to these challenges is to increase the utilisation of the potential of highly educated and skilled professionals widely available in these countries, i.e. pharmacists, who are well positioned to prevent and manage drug-related problems together with ensuring safe and effective use of medications with further care relating to medication adherence. Unfortunately, CPS are still underdeveloped and underutilised in some parts of Europe, namely in most of the Central and Eastern European (CEE) countries. This paper reviews current situation of CPS development in CEE countries and the prospects for the future of CPS in that region.